The Effect of The Teams Games Tournament (TGT) Cooperative Learning Model to Increase the Learning Interest of Pancasila Education for Class X Students of SMA 3 Blitar City - Prasetyo, Septiawan Sheva Putra; Cahyani, Arik; Rarasati, Ida Putri (Universitas Tanjungpura, 2024)
The purpose of this study was to analyze the impact of the Team Games Tournament (TGT) cooperative learning model on improving students' learning interest in Pancasila Education for Grade X students at SMA Negeri 3 Kota Blitar. The research employed an experimental method with a pre-test and post-test design. The sample consisted of 60 students divided into two groups: a control group and an experimental group. The experimental approach used a pre-test and post-test design, with 68 students divided into two groups: the experimental group (X-1) and the control group (X-7). Before conducting the study, a trial was conducted to determine the validity of the questionnaire. The validity and reliability tests showed reliability coefficients of 0.877 for the experimental group and 0.881 for the control group, both exceeding the threshold of 0.60. Data were collected using validated questionnaires and analyzed through assumption testing, including normality and heteroscedasticity tests. The normality test, conducted using the Kolmogorov-Smirnov method, yielded a significance value of 0.648, indicating that the data were normally distributed. The heteroscedasticity test produced a significance value of 0.976, suggesting no heteroscedasticity issues. Hypothesis testing was carried out using a partial t-test, which revealed that the TGT model had a significant positive effect on students' learning interest, as the t-value (2.095) exceeded the t-table value (2.036), and the significance value (0.039) was less than 0.05. These results support the hypothesis that TGT significantly influences students' learning interest. The study concluded that the TGT model effectively enhances student engagement and communication skills in the context of cooperative learning.